Attitudes towards Medically Assisted Reproduction among Students in Three Euro-Mediterranean Countries - Tutić Grokša, Ivana; Depope, Ana; Trako Poljak, Tijana; Buterin, Toni; Doričić, Robert; Rinčić, Iva; Gensabella, Marianna; Zagorac, Ivana; Eterović, Igor; Kalokairinou, Eleni; et al. (ETHICS IN PROGRESS, 2025)
Human reproduction has traditionally been an important issue in medical ethics. Advances in medical technology and the development of medically assisted reproduction (MAR) procedures are creating new bioethical dilemmas. This study is based on a quantitative approach using the survey method on a convenience sample of students (N=1097) from five universities from four fields of study – Medicine, Law, Theology and Philosophy – in Croatia, Greece and Italy. The aim of this study was to investigate students’ attitudes towards various aspects of medically assisted reproduction. Three hypotheses were tested using t-tests and ANOVA to examine differences in attitudes based on variables such as country, field of study, gender, year of study, religiosity, political orientation, financial status and size of their place of residence. Despite sharing a common Mediterranean cultural heritage, students from Italy showed a greater disapproval of MAR, but due to the small effect size, this difference should be interpreted with caution and the hypothesis could not be fully confirmed. In addition, Theology students had statistically significantly more negative attitudes toward MAR. Regarding differences in students’ socio-demographic characteristics, women, older students, individuals who are not religious and those who are politically left-oriented tended to have more liberal attitudes toward MAR. The results enable further reflection on the concept of Mediterranean Bioethics. These findings highlight how disciplinary background and religiosity shape ethical attitudes toward MAR within the Mediterranean context.